2018
DOI: 10.1016/j.neuron.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coding of Leg Proprioception in Drosophila

Abstract: Summary Animals rely on an internal sense of body position and movement to effectively control motor behavior. This sense of proprioception is mediated by diverse populations of mechanosensory neurons distributed throughout the body. Here, we investigate neural coding of leg proprioception in Drosophila, using in vivo two-photon calcium imaging of proprioceptive sensory neurons during controlled movements of the fly tibia. We found that the axons of leg proprioceptors are organized into distinct functional pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
201
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(217 citation statements)
references
References 83 publications
15
201
1
Order By: Relevance
“…4e) and identify the dorsally-branching clusters as motor neurons (Baek and Mann, 2009;Brierley et al, 2012) and the ventrallybranching clusters as sensory neurons (Tsubouchi et al, 2017). In some cases, we were also able to associate the neurons with specific sensory organs, such as the campaniform sensilla and femoral chordatonal organs (Mamiya et al, 2018). We observed that axons are spatially organized in the nerve, such that axons from neurons from the same morphological cluster tend to also physically cluster together within the nerve (Fig.…”
Section: Reconstruction Of Individual Neuron Morphologiesmentioning
confidence: 70%
See 2 more Smart Citations
“…4e) and identify the dorsally-branching clusters as motor neurons (Baek and Mann, 2009;Brierley et al, 2012) and the ventrallybranching clusters as sensory neurons (Tsubouchi et al, 2017). In some cases, we were also able to associate the neurons with specific sensory organs, such as the campaniform sensilla and femoral chordatonal organs (Mamiya et al, 2018). We observed that axons are spatially organized in the nerve, such that axons from neurons from the same morphological cluster tend to also physically cluster together within the nerve (Fig.…”
Section: Reconstruction Of Individual Neuron Morphologiesmentioning
confidence: 70%
“…The indicated motor neuron is the same neuron as in (h) (g) Cross-section through the femur. Asterisk denotes the femoral chordatonal organ, a proprioceptive sensory structure (Mamiya et al, 2018). (h) Detailed view of nerve within the femur, including a motor axon branching off to innervate a muscle (arrow).…”
Section: Millimeter-scale Xnh Imaging Of a Drosophila Leg At Single-nmentioning
confidence: 99%
See 1 more Smart Citation
“…Some hemilineages have dendritic processes restricted to specific sensory domains suggesting involvement in the processing of specific sensory modalities. For example, hemilineage 10B has dendrites tightly restricted to mVAC and intermediate neuropil indicative of being involved in processing of sensory information from the “club” type sensory afferents from the femoral chordotonal organ (FCO; Mamiya, Gunung, & Tuthill, ) and from campaniform sensilla on the legs. The 10B neurons also have intersegmental projections that overlap with the dendrites of their segmental homologs suggesting a role in coordinating sensory inputs between different legs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the broad expression of serotonergic receptors in sensory organs, it is 503 interesting that one of the behavioral roles of serotonin we identified is its ability to mediate the 504 response to vibration. Vibration is sensed by the chordotonal organ, and our expression 505 analysis reveals that serotonin receptors are expressed to different extents in chordotonal 506 neurons [100][101][102]. Together, these observations suggest that modulation of sensory 507 information as it is entering the VNC plays a key role in how serotonin modulates the response 508 to a vibration stimulus.…”
mentioning
confidence: 83%